PENGARUH PUTARAN TURBIN ANGIN SUMBU HORIZONTAL KOMBINASI PEMBERAT BOLA PEJAL - Firda Herlina; Mujiburrahman Mujiburrahman; Adi Asyari (Universitas Lambung Mangkurat, 2020)
Along with the increase in population is directly proportional to the need for energy sources both to support people's lives and the increase in the industrial sector in Indonesia. One of the most widely used sources of electricity is wind. Wind turbines are very sensitive to the wind speed they receive, as a result of fluctuations in wind speed that affect wind rotation speed. For this reason, the author has the idea to combine a wind turbine with a solid object turbine, it is hoped that the combination can produce more consistent rotation. The tool used is a wind turbine combined with solid blade ball weights 8, 9 and 10 and ballast of 10 gr, 20 gr and 30 gr for each blade and wind speeds of 3.3 m / s, 3.6 m / s and 3.9. m / s with the experimental research method, the experiment was carried out 3 times in each tool for ± 2 minutes which was expected to produce a combination of the variables studied in the form of a turbine with the maximum rotational speed and the most consistent rotation. From these experiments, it was found that a turbine with 10 blades, a weight of 10 gr at a wind speed of 3.9 m / s had the fastest rotation, namely 116.43 rpm while a 9 blade turbine with a weight of 30 gr at all three wind speeds was the turbine with the most consistent rotation, namely the difference between the top and bottom rotation is 2.53 rpm.